The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s13104-016-2246-5
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral primitive neuroectodermal tumors of the spine: a case report and review of the literature

Abstract: BackgroundPeripheral primitive neuroectodermal tumors are extremely rare tumors in the spine; only 18 cases of extra-dural peripheral primitive neuroectodermal tumor cervical region have been reported. The aim of this report is to highlight the challenges in diagnosis and management of this condition.Case presentationWe present a case of 5-year-old Moroccan boy, who presented with torticollis for 1 month. Computed tomography scan and Magnetic resonance imaging of the cervical spine revealed an extradural, dumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…An induction chemotherapy before tumor excision tends to reduce the tumor size, and also to control systemic disease. [ 2 ] But in intrathecal PNET, the blood–brain barrier prevents chemotherapeutic agents from gaining access to the tumor, making it difficult to treat. [ 9 ] In our case, no chemotherapy was given after the first operation under the consideration that chemotherapy with multiregimen might also have numerous side effects in children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An induction chemotherapy before tumor excision tends to reduce the tumor size, and also to control systemic disease. [ 2 ] But in intrathecal PNET, the blood–brain barrier prevents chemotherapeutic agents from gaining access to the tumor, making it difficult to treat. [ 9 ] In our case, no chemotherapy was given after the first operation under the consideration that chemotherapy with multiregimen might also have numerous side effects in children.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Although PNET is the second most common malignant neoplasm in childhood, the spinal cord, as primary site for PNET, is relatively rare in all age groups. [ 2 ] A large series of 430 patients showed that PNETs represent less than 1% of primary spinal tumors, [ 3 ] and according to the data from Taiwan Health Promotion Administration, there were only 2 patients with newly diagnosed PNET of nerve system in 2013. With reviewing publications, most reports on PNET focused on supratentorial PNET, whereas PNET affecting spinal location is extremely rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal PNET is a rare condition, but the incidence is increasing because of improved diagnostic modalities (13). Several cases of spinal PNET have been reported in the literature, mostly in children (4,6,7,15). However, epidural PNET is an extremely rare presentation with less than 15 cases reported in the literature (1-3,5,8,10-13).…”
Section: █ Discussionmentioning
confidence: 99%
“…PNETs of the central nervous system (CNS) have been reported in several locations including the cerebrum, cerebellum, brainstem, pineal gland, spinal cord and peripheral nerves (9,14,16). PNET of the spinal column is a rare condition and most of the reported cases are intramedullary (4,6,7,15,17). Only few cases of isolated epidural PNET have been reported in the literature, most of them in the children (2,3,10,11).…”
Section: █ Introductionmentioning
confidence: 99%